Gonadic Sperm Reserve in Buffaloes Created under Tropical Conditions - Siqueira, J. B. [UNESP]; Oba, Eunice [UNESP]; Pinho, R. O.; Castilho, E. F.; Bittencourt, R. F. [UNESP]; Assaf, S. S. [UNESP]; Guimaraes, J. D. (Pagepress Publ, 2007)
The objective of the present study was quantifying the spermatic production per gram and daily rate of the testicular parenchyma. Testis of 12 crossbred Murrah buffaloes aged 24 to 48 months created under extensive conditions in the State of São Paulo/Brazil were analyzed. Animals were divided into groups based on the testicular shape (long and long-moderate) and testicular sides (right and left) and the studied parameters were: length and testicular width, weight and volume of the albuginea and mediastinum and net weight of the testicular parenchyma, gonadic sperm reserves, spermatic production/g of testicular parenchyma, daily spermatic production/g, total daily spermatic production, resulting into the values: 8.16 +/- 0.87 and 4.29 +/- 0.50 cm; 9.09 +/- 1.91 g and 8.77 +/- 1.88 mL; 0.97 +/- 0.39 g and 0.90 +/- 0.38 mL; 112.91 +/- 18.85 g; 14.32 x 10(9) +/- 0.15; 13.42 x 10(6) +/- 0.17; 27.40 x 10(6) +/- 0.35 and 2.92 x 10(9) +/- 0.30, registering no difference between right and left testis in relation to the parameters (P>0.05). There was no relation between testicular biometry and spermatic production (P>0.05). According to the obtained values, all animals were considered sexually mature and presented an efficient spermatic production per gram of testicular parenchyma and total daily production.
Keywords: Buffaloes; Spermatic production; Gonadic sperm reserve